„Portret jednego człowieka”. Przyczynek do biografii Haliny Rząsowej (1924–1980), zakopiańskiej fotografki - Katarzyna Chrudzimska-Uhera (Załącznik Kulturoznawczy)
Although Halina Rząsa (1924–1980) was a photographer of considerable reputation in Zakopane, we are able to say next to nothing about her life and work. She is mostly remembered and mentioned as the wife and mother of two famous sculptors: Antoni Rząsa (1919–1980) and Marcin Rząsa (born 1965). The article looks at the history of the Zakopane artistic circles in order to reconstruct in detail the biography of this underappreciated artist. The author uses information and photographic material from a private family archive deposited in the Antoni Rząsa Gallery in Zakopane.